Strategi Funding dan Kepatuhan Syariah pada Pembiayaan Mudharabah: Studi pada BTN Syariah Cirebon - Muhammad Luthfi Hakim Saputro; Didi Sukardi; Toto Suharto (CIEBER: Contemporary Islamic Economic and Business Review, 2026)
The purpose of this study is to determine the marketing funding strategy for mudharabah financing and the. views of the DSN MUI fatwa on its implementation at BTN Syariah, Cirebon City. The research method used by the author is a qualitative method with a case study approach and data analysis techniques. In this study, the method of data reduction, data presentation, and conclusion was used. The results of this study are the Marketing Funding Strategy in Mudharabah Financing from the Perspective of the DSN MUI Fatwa in BTN Syariah. There are several ways, namely 1) Implementation of the marketing funding strategy by face. to face, door to door, utilizing social media such as Instagram, WhatsApp, and websites. In addition, it also uses selling marketing techniques and sales science techniques. 2) The. obstacles and efforts made by BTN Syariah Kota Cirebon include. obstacles such as the incompatibility of the products offered, public understanding, for the efforts made, always discussing with the head office or branches, and providing education to prospective. customers or the public. 3) The provisions of the DSN MUI Fatwa are already binding and have met the regulations given, so that the validity of its legality can be operated by BTN Syariah Kota Cirebon.